The Influence of Sharia Financial Literacy, Motivation, and Pocket Money on Investment Decisions in Sharia Mutual Funds - Syahputri, Diana; Muhammad Lathief Ilhamy Nasution; Wahyu Syarvina (Amkop Management Accounting Review (AMAR), 2025)
Islamic financial literacy, motivation, and pocket money are key factors that influence investment decisions in Islamic mutual funds. This study aims to identify and analyze the impact of Islamic financial literacy, motivation, and pocket money on investment decisions in Islamic mutual funds. The research method uses a quantitative approach. The data used in this study is primary data obtained from questionnaires. The sample of this study consists of active students of the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra, totaling 100 respondents. Data analysis techniques are performed using multiple linear regression to test the effect of independent variables on investment decisions. The results of the study indicate that Islamic financial literacy, motivation, and pocket money collectively have a significant effect on investment decisions in Islamic mutual funds.